THE BRAZILIAN SO KNOWN AMONG US”: THE CIRCULATION OF LOURENÇO FILHO WORKS IN THE LIBRARIES OF MEXICO (1933 - 1963) - do Nascimento Silva, Rony Rei [UNESP]; Nery, Ana Clara Bortoleto [UNESP] (FapUNIFESP (SciELO), 2022)
The text aims to analyze the circulation of the works of Lourenço Filho in Mexican libraries, in the period between 1933 and 1963. It is possible to affirm that the presence of these works in Mexico is indicative that they were part of the collections destined for the formation of normal schoolteachers, Primary Education leaders and school administrators, especially for offering readers principles of educational psychology, rural teacher training, experiences in Brazil and an overview of educational systems on a global scale. It can be concluded that the circulation of Lourenço Filho works in Mexican libraries is due to a network of relationships that he established with Mexican intellectuals, mediated by UNESCO and Crefal.
EL BRASILEÑO TAN CONOCIDO ENTRE NOSOTROS”: LA CIRCULACIÓN DE LAS OBRAS DE LOURENÇO FILHO EN LAS BIBLIOTECAS DE MÉXICO (1933 - 1963)
LE BRÉSILIEN TELLEMENT CONNU PARMI NOUS: LA CIRCULATION DES ŒUVRES DE LOURENÇO FILHO DANS LES BIBLIOTHÈQUES DU MEXIQUE (1933 - 1963)
Keywords: Crefal; Lourenço Filho; Mexico; UNESCO